2016
DOI: 10.1016/j.neubiorev.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive mechanisms for responding to mimicry from others

Abstract: unclear how the complex behavioural effects of mimicry relate to neural systems which respond to being mimicked. Mimicry activates regions associated with mirror properties, selfother processing and reward. In this review, we outline three potential models linking these regions with cognitive consequences of being mimicked. The models suggest that positive downstream consequences of mimicry may depend upon self-other overlap, detection of contingency or low prediction error. Finally, we highlight limitations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 176 publications
(241 reference statements)
6
78
0
Order By: Relevance
“…This study, as several other previous studies in a recent systematic review, lends further evidence to the reward‐related/positive response to being mimicked (Hale & Hamilton, ). It opens up broader theoretical questions on why should being mimicked lead to a reward‐related response.…”
Section: Discussionsupporting
confidence: 85%
“…This study, as several other previous studies in a recent systematic review, lends further evidence to the reward‐related/positive response to being mimicked (Hale & Hamilton, ). It opens up broader theoretical questions on why should being mimicked lead to a reward‐related response.…”
Section: Discussionsupporting
confidence: 85%
“…First, if imitation is being used as a social signal, what message is being sent? Previous work has suggested that imitation signals a desire to affiliate (Chartrand & Lakin, 2012) but positive effects of being imitated are not always seen (Hale & Hamilton, 2016a;Verberne, Ham, & Midden, 2015). Kinematic patterns can also signal informative intentions (McEllin, Sebanz, & Knoblich, 2018) or confidence (Patel, Fleming, & Kilner, 2012) which could be important here.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Sacheli and colleagues (2015) found that when interacting with an in-group but not an out-group avatar the actions of the other person interfered with people's own action execution and that this effect was mediated by participant's implicit racial bias. Further evidence of prejudice affecting bodily interaction with others come from studies of mimicry, the unconscious tendency we have to imitate the facial and bodily movements of others, which is thought to be a method of increasing affiliation (Chartrand & Lakin, 2013;Hale & Hamilton, 2016). This tendency to mimic another person is reduced when the person belongs to a social or racial out-group (Bourgeois & Hess, 2008;Liebert et al, 1972;Losin, Iacoboni, Martin, Cross, & Dapretto, 2012;Neely, Heckel, & Leichtman, 1973;van der Schalk et al, 2011;Weisbuch & Ambady, 2008), and the extent to which we mimic out-group members is negatively related to our implicit prejudice against them.…”
Section: Prejudice and The Bodily Selfmentioning
confidence: 99%